Conjuring up the Jinni - Ram, Rahesh R. (Architecture Image Studies, 2020)
This article focuses on my ongoing work within a collaborative project based on the enigmatic literary fiction ‘Tale of the Arabian Nights’. The book is a collection of tales from the Middle East dating back beyond the ninth century and profoundly influenced many writers such as Jorge Luis Borges and Italo Calvino.